Flow-Diversion for Ophthalmic Segment Aneurysms. Issue 3 (12th January 2015) - Zanaty, Mario; Chalouhi, Nohra; Barros, Guilherme; Schwartz, Eric Winthrop; Saigh, Mark Philip; Starke, Robert M.; Whiting, Alex; Tjoumakaris, Stavropoula I.; Hasan, David; Rosenwasser, Robert H.; Jabbour, Pascal
Abstract: BACKGROUND: The use of flow-diversion to treat ophthalmic segment aneurysms (OSA) has not been well evaluated. OBJECTIVE: To assess the visual outcomes, the obliteration rate, and the need for retreatment of OSA treated by the pipeline embolization device (PED). METHODS: Patients who underwent treatment with PED for OSA from 2009 to 2014 were selected and retrospectively reviewed. Patient's age, sex, mode of presentation, and aneurysm size were recorded. The complication rates, the need for retreatment (due to recurrence of the aneurysm or worsening symptoms), the aneurysm occlusion rates, the evolution of visual symptoms, and the evolution of headache/retro-orbital pain were registered. RESULTS: Forty-one patients harboring 44 OSA treated by flow-diversion were identified. Females constituted 87.80% (37/41) of the cohort. The mean age was 59.16 ± 12.54 years. At final angiographic follow-up, 77.27% (34/44) had complete occlusion, 6.81% (3/44) had near-complete occlusion, and 15.90% (7/44) had incomplete occlusion. Of the 22 symptomatic OSA, complete resolution or significant improvement was noted in 72.72% (16/22), while worsening of symptoms occurred in 4.54% (1/22). Five patients out of 22 (22.72%; 5/22) had no significant changes in their symptoms. The complication rate was 2.27% (1/44). The mortality rate was 0%. CONCLUSION: The low complication rate, the high obliteration rate, and the high rate of improvement in the visual symptoms make flow-diversion an appealing option for the treatment of OSA.